Halal Tourism: A Sharia Economic Perspective and its Impact on Local Economic Development - Adiba, Anggita Farah; Nisa, Fauzatul Laily (Li Falah: Journal of Islamic Economics and Business, 2024)
This study examines halal tourism from the perspective of Shariah economics, focusing on its potential to stimulate local economic growth, create new business opportunities, and improve community income and quality of life. Despite the growing interest in halal tourism, there is limited research on how it integrates with Shariah economic principles and its impact on local economies, especially in Muslim-majority countries like Indonesia. Using a qualitative literature review, this research synthesizes key studies on halal tourism and Shariah economics, emphasizing the principles of ownership, consumption, and distribution in the tourism sector. The study finds that halal tourism, when aligned with Shariah principles, can significantly contribute to economic development by creating jobs, boosting local businesses (such as hospitality, transportation, and retail), and increasing regional revenue, including local taxes and small business profits. Additionally, the research highlights that halal tourism encourages infrastructure improvements and enhances the overall quality of life for residents. The study's implications suggest that policymakers and tourism industry stakeholders should prioritize the development of Shariah-compliant tourism services, focusing on infrastructure, human resource training, and marketing to attract Muslim tourists and benefit local economies. By adopting these strategies, halal tourism can become a key driver of sustainable local economic growth, providing long-term social and economic benefits for communities.